SCHOOL-COMMUNITY COLLABORATION: AN EDUCATION MANAGEMENT APPROACH TO STRENGTHENING COMMUNITY-BASED SCHOOLS - Nurul Lail Rosyidatul Mu'ammaroh; Melyana R Pugu; Novia Nelza; Al-Amin (Prosiding Seminar Nasional Indonesia, 2024)
This research aims to analyse the importance of school-community collaboration as an educational management approach in strengthening community-based schools. The method used in this research is a literature review involving a review of various scholarly sources, journals and documentation related to this topic. The results show that effective collaboration starts with the establishment of a representative committee and a good communication strategy to ensure the involvement of all parties. Specific programmes such as mentoring, extracurricular activities and community service are proven to enrich students' learning experience and shape their character and social awareness. In addition, continuous evaluation and development through regular evaluation sessions and the use of relevant evaluation tools showed positive results in identifying areas of improvement and new opportunities. Overall, this study confirms that school- community collaboration is a strategic and effective approach to creating a comprehensive and inclusive education ecosystem. This collaboration not only optimises students' potential but also strengthens social ties within the community, making the educational process an ever-evolving collective effort.